Inaccuracy of the HR reserve vs. VO2 reserve relationship during prone arm-paddling exercise in surfboard riders - Mendez-Villanueva, A.; Perez Landaluce, J.; Fernandez Garcia, B.; Terrados, N.; Bishop, D. (Journal of Physiological Anthropology, 2007)
Abstract: Previous studies have demonstrated that during lower-body exercise the percentage of heart rate reserve (%HRR) is equivalent to the percentage of the oxygen consumption reserve (%VO2R) but not to a percentage of the peak oxygen consumption (%VO2peak). The current study examined these relationships in trained surfboard riders (surfers) during upper-body exercise. Thirteen well-trained competitive surfers performed a stepwise, incremental, prone arm-paddling exercise test to exhaustion. For each subject, data obtained at the end of each stage (i.e., HR and VO2 values) were expressed as a percentage of HRR, VO2peak, and VO2R respectively and used to determine the individual %HRR-%VO2peak and %HRR-%VO2R relationships. Mean slope and intercept were calculated and compared with the line of identity (slope=1, intercept=0). The %HRR versus %VO2R regression mean slope (0.88±0.06) and intercept (20.82±4.57) were significantly different (p<0.05) from 1 and 0, respectively. Similarly, the regression of %HRR versus %VO2peak resulted in a line that differed in the slope (p<0.05) but not in the intercept (p=0.94) from the line of identity. Predicted values of %HRR were significantly higher (p<0.05) from indicated values of %VO2R for all the intensities ranging from 35% to 95% VO2R. Unlike results found for lower-body exercise, a given %HRR during prone upper-body exercise was not equivalent to its corresponding %VO2R. Thus, to ensure more targeted exercise intensity during arm-paddling exercise, individual HR-VO2 equations should be used.